Comparing Assessment Methods of Attribute Importance in Teachers' Decisions: The Importance of Different Criteria for Tracking Recommendations after Primary School - Katrin Lintorf; Stefanie van Ophuysen; Igor Osipov (MDPI AG, 2021)
The importance of different criteria for tracking recommendations is usually inferred using regression weights as a cross-student measure. The few studies that have applied alternative approaches or differentiated between student groups sometimes reach different conclusions. According to research on judgment and decision making (JDM), different methods operationalize different facets of importance. Given this, we investigate whether the importance of criteria for tracking recommendations depends on a direct vs. indirect operationalization (regression weights vs. ratings). A total of 181 teachers selected four students from their most recent fourth-grade class using a 2 × 2 design (certain vs. uncertain qualification for the Realschule (vocational track) vs. the Gymnasium (academic track)). Then, they reported on the level and the importance of predetermined criteria for each student. Contrary to JDM research, we found few method-related differences, but striking differences between cases with a certain vs. an uncertain qualification. For the latter, the importance of the criteria is more homogeneous, the regression prediction is less successful and the importance varies with the dependent variable in the regression (actual recommendation vs. perceived qualification). We conclude that further research should focus on uncertain cases rather than method-related differences and suspect that, in uncertain cases, the formation of the recommendation is a multistage decision process.